Toxoplasmosis in Pregnant Women and HIV/AIDS Patients in Ethiopia: A Systematic Review and Meta-Analysis - Feleke, Daniel Getacher (J Parasitol Res, 2019)
BACKGROUND: Although Toxoplasma gondii infection in immune-competent individuals is usually asymptomatic or causes a mild flu-like illness, it may become severe and can occasionally be fatal in immune-compromised people, such as AIDS patients or pregnant women. METHOD: Electronic English databases (Pubmed, Google Scholar, Science Direct, and Scopus), parasitology congresses, and theses of Ethiopian medical universities, were systematically searched (published or unpublished data). Full-length articles and abstracts were collected using keywords such as Toxoplasma gondii, Toxoplasmosis, pregnant women, HIV/AIDS, and Ethiopia. RESULTS: Analysis of seroprevalence estimates was pooled using a random effects meta-analysis. Seventeen studies were included in the present systematic review and meta-analysis. One of these studies reported seroprevalence of T. gondii in HIV/AIDS patients and pregnant women. In this review, a total of 4,030 individuals were included and analyzed. The pooled prevalence of T. gondii in this review was 81.00% (95% CI = 69.10–89.78). Sub-group analysis showed that 2,557 pregnant women were evaluated. In pregnant women, the pooled sero-prevalence was 71.2 (95% CI = [51.9%, 87.1%]. In HIV/AIDS patients, 1,473 individuals were evaluated and the pooled seroprevalence was 88.45 (95% CI = 80.87%–94.31%). CONCLUSION: This systematic review and meta-analysis identified a high seroprevalence of Toxoplasma infection of 81% among immunocompromised patients. Scaling up prevention and control methods mainly strengthening educational efforts are necessary to avoid reactivation and to stop the spread of T. gondii infection.